Modeling bat prey capture in echolocating bats: The feasibility of reactive pursuit. (7th November 2018) - Vanderelst, Dieter; Peremans, Herbert
Highlights: The paper describes a computational model of prey pursuit in echolocating bats, the only mammals to hunt on the wing. In contrast to earlier work, we model head movements observed in bats. The responsiveness of the gaze direction allows bats to pursue and capture insects using reactive control. Abstract: Echolocating bats are the only mammals engaging in airborne pursuit. In this paper, we implement a reactive model of sonar based prey pursuit in bats. Our simulations include a realistic prey localization mechanism as well as a model of the bat's motor behavior. In contrast to previous work, our model incorporates bats' ability to execute rapid saccadic scanning motions keeping the prey within its field of view. Decoupling the flight direction from the gaze direction allows our model to capture erratically moving prey using reactive control. We conclude that the rapid shifts in gaze direction allow bats to deal with the narrow field of view provided by their sonar system.